EFFECT OF PREGNANCY ON THE DISEASE ACTIVITY IN ULCERATIVE COLITIS - Siddiqui, Aftab Ahmad; Mahboob, Amjad; Ansari, Moin; Alam, Intekhab; Bashir, Babar; Ahmad, Saeed (Journal of Postgraduate Medical Institute, 2011)
Objective: To study the effects of pregnancy on the disease activity in ulcerative colitis. Methodology: This experimental study was conducted at department of Medicine at Sultan Qaboos University Hospital Oman from July 2002 to December 2004. A total 60 diagnosed cases of ulcerative colitis proven on colonoscopy and biopsy and fairly well controlled disease at the time of enrollment were included in the study. Those who conceived and delivered during the study period were inducted as experimental group (total 30 patients), and those who did not conceive during the study period were inducted as control group (total 30 patients). Result: Out of total 60 patients, 30 patients who were included in the study group, 24 remained well with mild exacerbation requiring only increased dose of mesalamine, four patients had moderate disease exacerbation requiring oral steroids along with mesalamine. Two patients had severe exacerbation that was controlled on parental steroids. Among control group, 25 had mild exacerbation, 4 had moderate exacerbation and 1 had severe exacerbation during the study period. The eventual out come was good in all patients. Conclusion: It is thus concluded that a planned pregnancy when the disease is well controlled minimizes the risk of complications in patients of ulcerative colitis and also has got favorable outcome of pregnancy.